THE EFFECT OF CHILDHOOD IN THE FORMATION OF PERCEPTIONS ABOUT RELIGIOUS CONCEPTS: A CASE STUDY IN THE UNIVERSITY OF GUMUSHANE - Saffet KARTOPU (Fırat University, 2021)
In this study, the effect of childhood experiences in the formation of undergrad’ perception of religion are presented. In this context, the sample groups were randomly determined in the Gumushane University students. Correlate were examined which their mosque, religious man, God and the Koran concepts about current perceptions and experiences of childhood have been presented. Data parsing were benefited from percentage, frequency distribution and chi-square analysis and data evaluating was used SPSS (16.0) statistical software package. According to results of study while correlation reached statistically significance that with the perception of the mosque the mosque narrative of childhood, with exposed to violence in mosque don’t be afraid of going to the mosque, with the perception of religious functionary experience of religious functionary, with perception of God narrative of God in the childhood and with perception of Quran the narrative of the negative Quran; correlation don’t reached statistically significance that with perception of religious functionary the exposure severity of the religious functionary and affected by the severity of religious functionary, with the perception of God negative conception of God and effect of the negative narrative of God, with perception of Quran the narrative of the Qur'an and effect of the negative narrative Quran. In this study consists of two main parts. In the first chapter has focused on relationship between whether with thinkers their experiences in childhood perceptions of the religion. For this reason, some philosophers of the experiences in childhood have been examined how an impact on perceptions of their religion. In order to limit the issue have wined a seat an important place in the history of thought Spinoza, Kant, Nietzsche, Freud and Russell of experiences in the childhood have mentioned the impact of their ideas. Considered as part of the application in the second chapter is given study problems and subproblems, hypothesis, the universe and sample, limitations, resolution the research of findings, discussion, conclusions and recommendations of the study.